Tax incentives and environmental protection: Evidence from China's taxpayer-level data? - Jie Mao; Chunhua Wang (China Finance and Economic Review, 2016)
Background: Since 2008, China has provided ITC (investment tax credit) and TID (taxable income deduction) for firms who engage in investment or business related to reducing pollution emissions and saving energy. This paper examines both incidence and effects of these tax incentives. Methods: We use a unique panel dataset mainly from the NTSD (the National Tax Statistics Dataset of China) over 2007-2011, and utilize the Probit Model and the specification suggested by Greenstone (2002) to identify incidence and effects of the ITC and TID, respectively. Results: We find that: (1) The two tax incentives are generally not popular. SOEs are the main beneficiaries, while regional characteristics have no impact on taxpayers' attitude to ITC or TID. The mechanism behind may be that the incentives hurt interests of firms and local governments. (2) Their effects on taxpayers' activities including capital, employment, and production are not remarkable, while growth of coal consumption significantly speeds up. These findings are robust to multiple specifications of using different empirical strategies, samples, and variables. (3) However, the results indicate that the tax incentives do serve the purpose of protecting environment by restraining coal consumption in some specific group of firms who are affiliated to the central government. This finding confirms a simple model established in the paper that emphasizes the importance of the government' executive power on tax policies and relates to the literature finding that local support can remarkably boost the efficiency of tax incentives for environmental protection. Conclusions: According to the above findings, we conclude that the tax incentives such as ITC or TID can be effective tools to protect China's environment if correctively designed and adequately implemented.
Keywords: H23; Q58; H30; 330; Tax incentives; Environmental protection; China